The Moral Status of Human-Animal Chimeras with Human Brain Cells - Tannenbaum, Julie A. (The Hastings Center report, 2019)
While there is not unanimity (across time or cultures), almost all who read this commentary will think that both they and a toddler have a moral status higher than that of a rat. For instance, they will think that a third party who has to choose whom to save from death should choose them over the rat, and the toddler over the rat. But what is it about humans that gives us this greater moral status? This question is particularly pressing when considering that scientists have begun creating human-animal chimeras with brains composed partly or wholly of human cells. In “Human-Animal Chimeras: The Moral Insignificance of Uniquely Human Capacities,” Julian Koplin focuses on the moral implications of such experiments and those that use (or plan to use) these chimeras to study diseases and treatments. How should we understand the concerns about moral status that have been raised about such chimeras? In this commentary, I interpret these concerns differently from Koplin and respond to his suggestion that the greater one's ability to draw value from certain kinds of conscious experiences, the greater one's moral status.